Task-Supported EFL Instruction: Integrating Students, Teacher, and Textbook Roles in a Japanese Mainstream High School Class - Alvin Ibe Santos (Universitas Pendidikan Mandalika, 2023)
Today in Japan, the impetus to effect positive change on students’ use of English as a communication tool is reflected in the thrust of the Ministry of Education to promote meaningful in-class practice as highlighted in the revised high school foreign language curriculum. However, teachers face a dilemma of implementing meaningful classroom practice of English entirely without any focus on grammar or form. Fortunately, an approach which may offer a balanced opportunity to create meaningful practice while highlighting the target expression in use is Task-supported language teaching (TSLT). To better understand TSLT’s usefulness in an EFL setting, this classroom-based research explores the potential roles that students, the teacher, and the textbook play in a sociocultural approach-oriented EFL class employing TLST and how it complements a Japanese mainstream high school class. Utilizing mixed methods of sociocultural discourse analysis and self-reporting of Grade 11 (n=117) mainstream EFL learners, results indicate that: the students, talking in pairs using their L1, (1) understood difficult vocabulary, (2) managed assigned tasks, and (3) engaged in off-task dialogue; the teacher performed the roles of (1) classroom manager, (2) communicator of content, and (3) assessor and provider of feedback; and the textbook played (1) informative, (2) instructional, and (3) experiential roles in the classroom. It was also found that TLST complements a Japanese high school mainstream EFL class by (1) optimizing the limited time offered in class for students to tackle the TL; (2) aiding students in their standardized institutional exams; and (3) appealing to Japanese cultural sensibilities.